Quelles voies pour la participation du public à la conservation de la nature ? Le cas des réserves de biosphère - Jean-Eudes Beuret (Développement Durable et Territoires)
The general public can help to conserve nature in many different ways, as shown by the comparative analysis of twelve biosphere reserves carried out in ten countries. This may be in the form of a contributive participation, a participation limited to information or consultation operations, a real negotiation or measures by which managers of biosphere reserves try to encourage independent initiatives and create innovative settings for discussion on nature conservation. This article presents the conceptual framework and the analytical approach and then describes the range of schemes set up to allow the participation of the public. It then looks at the key questions to be answered when setting up discussions between environment and development, in a sustainable development perspective.